Sr2MgOsO6: A frustrated Os6+ (5d2) double perovskite with strong antiferromagnetic interactions - Sarapulova, Angelina; Adler, Peter; Schnelle, Walter; Mikhailova, Daria; Felser, Claudia; Tjeng, Liu Hao; Jansen, Martin (Zeitschrift für Anorganische und Allgemeine Chemie, 2015)
The Os6+ (t2g2) double perovskite Sr2MgOsO6 was prepared as polycrystalline material from the respective binary metal oxides. Sr2MgOsO6 crystallizes with the tetragonal space group I4/m. Magnetization and specific heat measurements show a broad anomaly near 100 K, but no well-defined cusp. The magnetism is governed by strong antiferromagnetic interactions. Sr2MgOsO6 constitutes a new example for the peculiar, poorly understood magnetism of 5d2 ions on a frustrated fcc lattice, where spin-orbit coupling and orbital physics are expected to play an important role.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Antiferromagnetism; Double perovskite oxides; Magnetic frustration; Osmium; Spin-orbit coupling